PENINGKATAN KAPASITAS TENAGA KEPENDIDIKAN DALAM PENGELOLAAN WEBSITE BILINGUAL PADA JURUSAN MANAJEMEN DI UNIVERSITAS ANDALAS - Ares Albirru Amsal; Venny Darlis (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
A bilingual website is an essential component in delivering information in today's digital era. The existence of a website as a credible reference for information can support the implementation of a good organization and improve reputation in the national and international scope. Because of the significant benefits of the website, every organization is required to have a representative website, including educational institutions such as the Department of Management, Faculty of Economics, Andalas University. Therefore, increasing the capacity of education personnel in managing the website is an urgent thing to do. To achieve this, this activity does modules and provides training for department employees to have basic skills in managing the department's website. Before carrying out the activity, problem identification and finding solutions were carried out using the USG (Urgency, Seriousness, Growth) method, followed by a root problem tree and SMART analysis (Specific, Measurable, Achievable, Relevant, Time-bound). After that, module creation, training, and evaluation are carried out simultaneously. The result of this activity is that the Management Department has a module for website management, and education personnel has increased their website management skills. Education staff feel the benefits of modules and training even at the primary level. It is hoped that in the future, assistance will still need to be carried out to ensure the website remains managed and becomes a means of consultation if education personnel experience problems.